Evolution, function and roles in drug sensitivity of trypanosome aquaglyceroporins - Quintana, Juan F; Field, Mark C (Parasitology, 2021)
Aquaglyceroporins (AQPs) are membrane proteins that function in osmoregulation and the uptake of low molecular weight solutes, in particular glycerol and urea. The AQP family is highly conserved, with two major subfamilies having arisen very early in prokaryote evolution and retained by eukaryotes. A complex evolutionary history indicates multiple lineage-specific expansions, losses and not uncommonly a complete loss. Consequently, the AQP family is highly evolvable and has been associated with significant events in life on Earth. In the African trypanosomes, a role for the AQP2 paralogue, in sensitivity to two chemotherapeutic agents, pentamidine and melarsoprol, is well established, albeit with the mechanisms for cell entry and resistance unclear until very recently. Here, we discuss AQP evolution, structure and mechanisms by which AQPs impact drug sensitivity, suggesting that AQP2 stability is highly sensitive to mutation while serving as the major uptake pathway for pentamidine.
Keywords: Aquaglyceroporin; pentamidine; Drug Resistance; Aquaglyceroporins; membrane trafficking; drug resistance; Protozoan Proteins; Trypanocidal Agents; protozoální proteiny; akvaglyceroporiny; sleeping sickness; léková rezistence; Trypanosoma; Trypanosoma brucei; trypanocidální látky